Are news outlets viewed in the same way by experts and the public? A comparison across 23 European countries - Schulz, A; Fletcher, R; Popescu, M (Reuters Institute for the Study of Journalism, 2020)
In this RISJ Factsheet, we compare expert evaluations of news outlets'; accuracy from the 2017 European media systems survey (Popescu et al. forthcoming) with the Digital News Report 2018 audience brand trust scores (Newman et al. 2018). Our analysis shows a strong positive correlation at the outlet level between public trust and accuracy assessments by experts. On average, both experts and the public rate news from public service media outlets as the most accurate and the most trustworthy, respectively. News from digital-born brands is on average rated lower by both. Commercial TV and newspapers sit between the two for both experts and the public. Although public and expert ratings are broadly consistent, relative to what we would expect based on expert opinion of accuracy, TV outlets appear to be slightly more trusted by the public, whereas newspapers and digital-born outlets appear to be slightly less trusted.